CLOUD INTEGRATION PLATFORMS AS A SERVICE (iPaaS) AND AUTOMATION: A TECHNICAL OVERVIEW - Mahaboob Subhani Shaik (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY, 2024)
Integration Platforms as a Service (iPaaS) have emerged as transformative solutions in the modern digital landscape, enabling organizations to connect cloud seamlessly and on-premises systems while ensuring efficient data synchronization and process automation. This comprehensive article explores the core components, key features, implementation considerations, and future trends of iPaaS solutions. The article examines how iPaaS platforms address complex integration challenges through advanced runtime environments, sophisticated connector frameworks, and robust data transformation capabilities. It further investigates the business and technical benefits of iPaaS adoption, including accelerated market delivery, cost optimization, and improved developer productivity. The article also delves into critical implementation considerations and emerging technological trends reshaping the iPaaS landscape, highlighting the strategic importance of these platforms in driving digital transformation initiatives across various industries.